THE INFLUENCE OF EXPERIENTIAL MARKETING, EXPERIENTIAL VALUE AND BRAND TRUST ON CUSTOMER SATISFACTION TELKOMSEL SIMPATI CARD IN THE CITY OF LHOKSEUMAWE - Asbar, Yuli; Biby, Sapna; Razif, Razif; Nurhayati, Nurhayati (RADJA PUBLIKA, 2022)
This study aims to see the effect of Experiential Marketing, Experiential Value and Brand Trust on Customer Satisfaction with Telkomselsel Simpati Card in Lhokseumawe City. The data used in this study is primary data, the sample in this study was 97 sympathy card customers. The sampling technique used is the purposive sampling. The method used to analyze the relationship between the independent variable and the dependent variable is the multiple linear regression method. The results of the study partially experiential marketing variables affect customer satisfaction at Telkomselsel in Lhokseumawe City. The experiential value variable has an effect on satisfaction Customers on Telkomsel in Lhokseumawe City. Brand trust variable has an effect on customer satisfaction at Telkomselsel in Lhokseumawe City. And simultaneously experiential marketing, experiential value, brand trust variables have an effect on customer satisfaction at Telkomselsel in Lhokseumawe City.